الحداثة في شعر محمود درويش - غنيم غسان; سعيد مبارك (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
يهدف هذا البحث إلى توضيح مسألة الحداثة الشعرية عند محمود درويش ، والوقوف على دلالاتها ، وإلى رصد ما للقصيدة عنده من دور في رسم معالم رؤيا متميزة في محبة الأرض والإنسان . وتعد هذه الرؤيا الجديدة تطوراً لواحدة من إيجابيات الشعر العربي في العصر الحديث ، حيث خرج الشعراء عن النهج التقليدي في وحدة البيت والقصيدة قديماً ، فنمت الملكات الفكرية ، وامتلك كثيرون رؤى فنية مغايرة للقديم. فالحداثة نقلة نوعية انعكست على الأدب عامة ، وعلى الشعر الحديث بخاصة ، لأن الشعر يملك على مر الزمان أكبر هامش من الحرية ، من خلال صوره ورموزه وتعابيره ، وبذلك أضحت القصيدة الحديثة وحدة عضوية، وغدت بتشكيلها الخارجي ومضمونها تجربة فنية إبداعية جميلة . This research aims at exploring the issue of Mahmoud Darwish’s poetic modernism, highlighting the role the poem plays in bringing out distinctive visions of love for land and Man. This new vision is considered a reflection of the positive sides of Arabic poetry in modern time. When poets find out new ways out of the traditional frame in the unity of line and that of the poem, so a fresh mentality has emerged, and so many poets have obtained new artistic visions that are quite unlike the old ones. Modernism is regarded as a distinctive step reflected on literature in general, and on poetry, in particular; since poetry has, through its symbolic images and expressions, a wide margin of freedom throughout. the modern poem has become an integral part both in form and content..